A novel SPINK5 mutation and successful subcutaneous immunoglobulin replacement therapy in a child with Netherton syndrome. Issue 6 (7th August 2020) - Zelieskova, Maria; Banovcin, Peter; Kozar, Marek; Kozarova, Andrea; Nudzajova, Zuzana; Jesenak, Milos
Abstract: We report a 2‐year‐old patient with Netherton syndrome presenting with generalized exfoliative erythroderma, ichthyosiform dermatitis, trichorrhexis invaginata, hypernatremic dehydration, failure to thrive, and recurrent respiratory infections. Molecular analysis of SPINK5 identified a novel mutation (c.1530CA). Our case report also verifies and supports the safety and efficacy of subcutaneous immunoglobulin substitution in chronic generalized skin disorders associated with primary immunodeficiencies such as Netherton syndrome.